Dietary patterns and PFAS plasma concentrations in childhood: Project Viva, USA. (June 2021) - Seshasayee, Shravanthi M.; Rifas-Shiman, Sheryl L.; Chavarro, Jorge E.; Carwile, Jenny L.; Lin, Pi-I D.; Calafat, Antonia M.; Sagiv, Sharon K.; Oken, Emily; Fleisch, Abby F.
Highlights: Children with a diet of frequently packaged foods and fish had higher PFAS. Ice cream and soda were key components of the packaged foods and fish diet. Findings may reflect novel PFAS sources or correlated lifestyle/toxicokinetic factors. Abstract: Background: Diet is thought to account for most adult human exposure to per- and polyfluoroalkyl substances (PFAS). Children are particularly vulnerable to adverse health effects of PFAS and may have different eating habits than adults. However, studies of dietary patterns and PFAS in children are limited. Methods: We studied 548 Boston-area children with food frequency questionnaire data (89 food items) in early childhood (median age 3.3 years) and plasma concentrations of 6 PFAS quantified in mid-childhood (median age 7.7 years). We used univariate linear regression to examine associations between each food item and PFAS, accounting for multiple comparisons. We next used reduced rank regression (RRR) to estimate overall percent variation in PFAS explained by diet and identify dietary patterns most correlated with PFAS. All models were adjusted for race/ethnicity, maternal education, and household income. Results: In univariate analyses, 2-(N-methyl-perfluorooctane sulfonamide) acetate (MeFOSAA) plasma concentrations were 17.8% (95% CI: 7.2, 29.5) and 17.0% (95% CI: 6.4, 28.7) higher per SD increment in intake of ice cream and soda, respectively. RRR identified 6 dietary patterns that together explained 18% variation in the plasma concentrations of the 6 PFAS, of which 50% was explained by a dietary pattern consisting of primarily packaged foods (including ice cream and soda) and fish. Children with higher intake of the packaged foods and fish dietary pattern had higher plasma concentrations of all PFAS, particularly MeFOSAA and PFOS. Conclusions: Our analysis examined food intake in association with several PFAS in children and identified dietary determinants that may be sources of PFAS exposure or reflect correlated lifestyle or toxicokinetic factors. Further investigation may help inform measures to modify childhood PFAS exposure.